Fluctuation relations in non-equilibrium stationary states of Ising models - Piscitelli, Antonio (2015)
Fluctuation relations for the entropy production in non-equilibrium stationary states of Ising models are investigated by means of Monte Carlo simulations. Systems in contact with heat baths at two different temperatures or subject to external driving will be studied. In the first case, considering different kinetic rules and couplings with the baths, the behaviors of the probability distributions of the heat exchanged in time τ with the thermostats, both in the disordered phase and in the low temperature phase, are discussed. The fluctuation relation is always followed in the large τ limit and deviations from linear response theory are observed. Finite τ corrections are shown to obey a scaling behavior. In the other case the system is in contact with a single heat bath, but work is done by shearing it. Also for this system, using the statistics collected for the mechanical work we show the validity of the fluctuation relation and the preasymptotic corrections behave analogously to those for the case with two baths.